INDEPENDENT COMPOST HOUSE AS A SUSTAINABLE URBAN ORGANIC WASTE MANAGEMENT MODEL - Dwi Haryanta; Fungki Sri Rejeki; Endang Retno Wedowati (Yayasan Education and Social Center, 2022)
Neighborhoods or urban villages do not have facilities to dispose of or process tree-changing waste carried out by residents, which is prone to causing social, environmental health, and aesthetic problems. Independent composting houses expect a solution in the form of a mass composting program but on a scale still affordable at the RW or district level. One composting process unit with a volume of one cubic meter is capable of processing three trucks of intermediate waste—the introduction project conducted in RW 02 Kalirungkut, Surabaya City. Residents ask to collect the chaffing waste at a point, and after 1-2 months, thresh. The composting equipment consists of an iron frame with one cubic meter volume and a cubic meter composting bag. Following the threshing, the dry leaves were collected and placed in the bag along with an activated EM4 solution starter. After all the components add, the bag zips up, the content does not mix, and it places in the incubator for three months. After the incubation period, the material will change color to blackish brown, the structure will become crumbly, and the temperature will be the same as the surrounding air temperature as a sign that the compost is ready to be harvested. The harvested compost is put in small bags weighing 15-20 kg, ready to be distributed to residents or sold to the general public. Residents can use the compost to grow fruits, vegetables, or ornamental/garden plants. The spirit of the residents of RW 02 Kalirungkut Surabaya City continues to be encouraged to continue the independent compost house program by monitoring, assisting, and providing incentives, especially in the distribution of excess compost used by residents